Pengaruh Operating Capacity dan Working Capital Turnover Terhadap Financial Distress - Shinta Fabrian; Nelvirita Nelvirita (Jurnal Eksplorasi Akuntansi, 2024)
Financial distress is a decline in a company's financial condition that occurs before bankruptcy or liquidation, which begins with the company's inability to fulfill its obligations. Based on data on the Indonesian Stock Exchange, several companies have experienced bankruptcy for two consecutive years in mining sector companies in 2019-2022. The aim of this research is to determine the effect of operating capacity and working capital turnover on financial distress. This type of research is quantitative with documentation methods. The total population is 86 companies with a sample of 39 companies. The sample was selected using a purposive sampling method, the data used were the annual financial reports of various mining sectors for the 2019-2022 period. Data analysis uses classical assumptions, T test and F test and multiple linear regression analysis using the Altman Z-Score method. The results of this research show that operating capacity has a positive and significant effect on financial distress and working capital turnover has no significant effect on financial distress.